The Fiction of Truth : Structures of Meaning in Narrative and Dramatic Allegory - Van Dyke, Carolynn (Cornell University Press, 2019)
The Fiction of Truth offers a rigorous reexamination of allegory. Rejecting the traditional notion that allegory says thing and means another, Carolynn Van Dyke proposes a new definition of the genre, derived both from contemporary critical theory and from the practice of medieval and Renaissance allegorists. Allegories, Van Dyke asserts, differ from other kinds of narrative in the syntactic rules that seem to generate their plots. Through a reading of Prudentius' Psychomachia, the earliest allegory, Van Dyke formulates a semiotic code that she finds implicit in allegorical works. She shows how allegorists adopted and altered that code in such works as The Romance of the Rose, medieval morality plays, The Pilgrim's Progress, The Divine Comedy, and The Faerie Queene. Her book is both a bold theoretical examination of allegory and a history of its evolution over the twelve centuries during which it played a major-even a dominant-role in Western literature.